Tuberculosis of seminal vesicles: a rare case report - Hicham El Boté; Abdelmounim BOUGHALEB (IDCases, 2025)
Tuberculosis of seminal vesicles is an uncommon form of genitourinary tuberculosis, frequently presenting with nonspecific symptoms and posing diagnostic challenges. Herein is reported a case of a 33-year-old male with a history of pulmonary tuberculosis in childhood who presented with nonspecific urinary symptoms. Imaging and histopathological findings confirmed tuberculosis of the seminal vesicle. This case underscores the importance of considering tuberculosis in the differential diagnosis of genitourinary symptoms, especially in patients with a prior history of tuberculosis. Early diagnosis and timely treatment are important to prevent complications and improve outcomes.